Compliance: Politics, Sociability and the Constitution of Collective Life. Issue 1 (1st July 2021) - Rollason, Will; Hirsch, Eric
Abstract: What kind of phenomenon is it when ordinary people in the United Kingdom unexpectedly abide by government advice on social distancing in response to the COVID-19 pandemic, even anticipating constraints on their activities? These happenings demand that we engage anthropologically with compliance – acts or activities that conform, submit or adapt to rules or to the demands of others. At present, there is no 'anthropology of compliance'. Rather, the discipline has inherited traditions of thought about compliance – as a necessary aspect of sociability or a morally suspect complicity, demanding resistance. These assumptions remain unexamined, but profoundly shape anthropological scholarship. This introduction aims to show how and why compliance might be a useful heuristic for anthropology. We define compliance as that set of means by which actors strive to accommodate themselves to others in their collective life . We argue that this conception of compliance allows us to multiply the kinds of phenomena we can call 'political'. It allows us to think about the political constitution of 'radical' difference, but to avoid making people identical with their cultural or conceptual worlds. By showing what compliance is and how it operates in and on social life, we ought therefore to be able to recover both specific forms of suffering and inequality and the ways in which social lives are constitutively different.